Control spending in hospital supplies of common use in Central Hospital (2014)
This essay arises from the need to determine how to improve the existing tools to quantify the actual expenditure of the elements commonly used in hospital Central. The elements of common hospital use as the name suggests are commonly used in the institution and are required for normal operation of the hospital, these hospitals are established elements within the group of medical devices for the attention, care and restoration of health in turn are divided into elements of reuse and elements which are designed for single use. Important for the acquisition of such elements which category do not have an effective tool evidencing control spending or consumption of these reserves in the budget for the Central Hospital